Pengabdian Mahasiswa KKN di Desa Sumber Arum Dusun II Masjid Al-Matin: Mewujudkan Desa yang Agamis, Bersih, dan Kreatif - Zulfikri Muhammad; Putri Nurhidayah; Maratuz Solihah; Sofya Agustina; Naurah Zahra; Siti Ulil Mutmainah; Dona Fionita; Yuyun Siti Rahmawati; Adhi Solekhan; Egge Jumzen; Darmison Vebi Hipriawan (Jurnal Kemitraan Masyarakat, 2024)
KKN activities in Sumberarum Village Hamlet II are directed at realizing a more religious, clean, and creative village. The main issues identified were the lack of community participation in religious activities, lack of awareness of the importance of environmental hygiene, and limited economic opportunities for the community. The research objectives include increasing community participation in religious activities, increasing awareness of the importance of environmental cleanliness, empowering the community through handicraft training, and encouraging young children to recognize themselves. The research methods used include observation, interviews, documentation, and evaluation. The programs carried out include religious competitions in the month of Muharram, mutual cooperation for environmental empowerment, self-introduction education for kindergarten children, making signposts for the kadun, RT / RW, and mosque, and training in making handicrafts from palm trunks. The results of these activities show an improvement in the quality of community life, among others reflected in the increased participation in religious activities, the realization of a cleaner and more organized environment, and the growth of community interest in developing handicraft businesses. In addition, educational activities for kindergarten children also have a positive impact on child development.